Ferrita de cobre recoberta com dióxido de titânio (cufe2o4/tio2) aplicada na degradação fotocatalítica do corante azul de metileno - Castro, Adeildo Batista Queiroz de (2016)
It is known that titanium dioxide (TiO2) shows excellent results in photocatalytic processes. In order to improve the process of recovery of the same in the present work, TiO2 was coated on copper ferrite (CuFe2O4). The CuFe2O4, ceramic material with magnetic properties, was synthesized by Pechine method (polymeric precursors), and calcined at 900 °C. Refinement of data from X-ray diffraction (XRD) of CuFe2O4 sample was made and it was noted the presence of the tetragonal phase and the cubic space groups. In order to obtain information that could relate to the characteristics of the material synthesized with the results presented in photocatalytic tests, other characterizations of samples were carried out such as: Reduction in temperature programmed, isotherms of adsorption and desorption of N2 and X-Ray Fluorescence. TiO2 fixation process in CuFe2O4 was done in order to evaluate photocatalytic performance of TiO2 in impregnated form, as well as to recover post-test material using separation techniques for separating and / or by the action of magnetic field. The characterization analyzes of post-test materials show that the crystalline phases are stable, and this suggests that the catalyst can be reused. The catalyst reuse tests were performed and the results indicated that the process can be applied. The data obtained in the analysis of material characteristics, associated with the observations noted in photocatalytic tests, contributed to justify the evaluative assumptions built throughout the work. In the tests cited above, but others were made by varying the concentration of the catalyst and also by varying the dye concentration. All photocatalytic tests were performed using the dye methylene blue (C16H18ClN3S) as a probe molecule. In general, this study showed that, making use of the characteristics of the materials involved in the process, we can give more practical and have a better use of titanium dioxide catalyst, especially considering their recovery and / or its reuse.